Cost-effectiveness analysis of capecitabine maintenance therapy plus best supportive care vs. best supportive care alone as first-line treatment of newly diagnosed metastatic nasopharyngeal carcinoma - Han, Jiaqi; Lan, Xiaomeng; Tian, Kun; Shen, Xi; He, Jinlan; Chen, Nianyong (Frontiers in Public Health, 2023)
Objectives Maintenance therapy with capecitabine after induction chemotherapy for patients with newly diagnosed metastatic nasopharyngeal carcinoma (mNPC) has been confirmed to be effective. This study aimed to evaluate the cost-effectiveness of capecitabine as maintenance therapy for patients with mNPC from the Chinese payers' perspective. Methods Markov model was conducted to simulate the disease progress and evaluated the economic and health outcomes of capecitabine maintenance plus best-supported care (CBSC) or best-supported care (BSC) alone for patients with mNPC. Survival data were derived from the NCT02460419 clinical trial. Costs and utilities were obtained from the standard fee database and published literature. Measured outcomes were total costs, quality-adjusted life-years (QALYs), life-years (LYs), incremental cost-utility ratios (ICURs), incremental cost-effectiveness ratios (ICERs), incremental net monetary benefit (INMB), and incremental net-health benefit (INHB). Sensitivity analyses were performed to assess model robustness. Additional subgroup cost-effectiveness analyses were accomplished. Results Throughout the course of the disease, the CBSC group provide an incremental cost of $9 734 and additional 1.16 QALYs (1.56 LYs) compared with the BSC group, resulting in an ICUR of $8 391/QALY and ICER of $6 240/LY. Moreover, the INHB was 0.89 QALYs, and the INMB was $32 034 at the willingness-to-pay threshold of $36 007/QALY. Subgroup analyses revealed that CBSC presented a positive trend of gaining an INHB in all subgroups compared with the BSC group. The results of sensitivity analyses supported the robustness of our model. Conclusion Compared with BSC, after induction chemotherapy, CBSC as a first-line treatment was cost-effective for newly diagnosed mNPC. These results suggest capecitabine maintenance therapy after induction chemotherapy as a new option for patients with newly diagnosed mNPC.